A population based, prospective study of the development of ROP in prematurely born children in the Stockholm area of Sweden. Issue 7 (July 1993) - Holmström, G.; el Azazi, M.; Jacobson, L.; Lennerstrand, G.
Abstract : A prospective population based study including 260 children with a birth weight of 1500 g or less was performed in the Stockholm county. The total incidence of retinopathy of prematurity (ROP) was 40.4%, while severe ROP–that is, stage 3 or more, was seen in 20.0%. Cryotherapy was performed in 10.8%. Logistic regression analysis revealed independent association of both gestational age and birth weight with ROP. The association of gestational age and ROP was significantly stronger, indicating that the degree of immaturity of the eye is a main predictive factor for the development of ROP. The purpose of a general screening for ROP is to identify children requiring cryotherapy. Based on these results it seems appropriate to include children with a gestational age of 32 weeks or less in such a programme and a first examination at 5-6 weeks of postnatal age is suggested.